Fa’āliyah Madkhal Alta’alīm Walta’alum Alsiyāqī Fī Ta’lim Almufradāt Al’arabiyah Litalāmidz Alshafi Alsādis Fī Almadrasah Al ibtidāiyah Alhukūmiyah Al ūlā Binkālān - Taqyuddin Ibnu Syafi’I CM; Ahmed Abdelrazek El Khateb (Lembaga Penelitian dan Pengabdian Masyarakat, Sekolah Tinggi Ilmu Bahasa Arab Ar Raayah, 2022)
The elementary school period is the most important period in enriching vocabulary. This study aims to determine the effectiveness of the learning for the sixth grade students of Madrasah Ibtidaiyah Negeri 1 Bangkalan. The researcher uses an experimental method with pre-test and post-test to determine the effectiveness of the teaching and learning approach. This study was applied to a research sample consisting of 29 students in one group, The results of the study resulted in the expected effectiveness in using a contextual learning approach. It is concluded from the results of the comparison of the pre-test scores of the sixth graders that the total score is 1915 with an average of 66,34 and the results of the post-test scores with a total of 2440 with an average 84,13. Therefore, the difference in the post test score is 525 while the difference in the average score is 18,11 shows that the use of contextual teaching and learning methods is effectively used for teaching Arabic language vocabulary. Masa sekolah dasar merupakan masa terpenting dalam memperkaya kosakata. Penelitian ini bertujuan untuk mengetahui keefektifan pembelajaran pada siswa kelas VI Madrasah Ibtidaiyah Negeri 1 Bangkalan. Peneliti menggunakan metode eksperimen dengan pre-test dan post-test untuk mengetahui keefektifan pendekatan belajar mengajar. Penelitian ini diterapkan pada sampel penelitian yang terdiri dari 29 siswa dalam satu kelompok, Hasil penelitian menghasilkan efektivitas yang diharapkan dalam menggunakan pendekatan pembelajaran kontekstual. Dari hasil perbandingan nilai pre-test siswa kelas VI disimpulkan bahwa total nilai 1915 dengan rata-rata 66,34 dan hasil nilai post-test total 2440 dengan rata-rata 84 ,13. Oleh karena itu, selisih nilai post test sebesar 525 sedangkan selisih rata-rata skor sebesar 18,11 menunjukkan bahwa penggunaan metode pembelajaran kontekstual efektif digunakan untuk pengajaran kosakata bahasa Arab.